Community Participation in Policy Implementation Green Open Spaces of Kampung City Settlement - Muhammad Agus Syukron (Budapest International Research and Critics University, 2022)
The characteristics of a city according to some planologists lay on open space, not malls, shops, or even shopping centers. In relation with city development, the flow of urbanization and the increasing dwelling needs out of government control, while the urban economical level is limited. In order to solve environmental problems as result of development programs, it needs planning and community participation to support the conditions and city needs. The involvement of society is significantly important as a responsibility to build good corporate governance, outside the government and private bodies. The objectives of the current study were to analyze the various correlations of community participation forms toward the implementation of green space residence policy and to analyze the effect of community participation toward the implementation of green space residence policy in Kecamatan Klojen, Kota Malang. The researcher uses proportionale stratified random sampling to take 80 members of ‘karang taruna’, ‘PKK or Dasa Wisma’, and informal leaders as survey samples. Then, the author tests the hyphotheses on the relationship among variables by association testing through Path Analysis. It is found that community participation in Kecamatan Klojen, Malang toward policy implementation of green space residence classified high, in order to create a beautiful scenery (aesthethics function), pleasant and healthier (socio-culture function), also cool environment (ecological function). It is reveals that the lag economic and education background are not always have relation with the ignorance of environmental existing condition. Another result found that community independence, human readiness, and the decision making have significant and dominant effect toward the policy implementation of green space residence, as a collective responsibility (“Gotong Royong” culture).